Morphologic differences of occipital region in patients with schizophrenia and migraine headache using magnetic resonance imaging (MRI) and visual evoked potentials (VEPs) - Gorana Sulejmanpašić; Saida Fišeković; Senad Drnda (Medicinski glasnik, 2017)
Aim: To compare morphologic variations of occipital sulci patterns in patients with schizophrenia and migraine headache regarding gender and laterality using magnetic resonance imaging (MRI) and visual evoked potentials (VEPs) as well as damage of visual pathway in patients with schizophrenia. Methods: This study included 80 patients. Brain scans and visual evoked potential responses recorded over the occipital cortex were performed to analyze the occipital region of both hemispheres. Average total volumes of both hemispheres and average values of latency of the healthy population were used for comparison. Results: There was statistically significant difference between subjects considering gender (p=0.012). Parameters of body of the calcarine sulcus (p=0.0325) showed statistically significant positive correlation with P100 latency (p=0.0449), inferior sagittal sulcus (p=0.0443) had significant positive correlation with P100 latency (p=0,0413), lateral occipital sulcus (p=0.0411) and P100 latency (p=0.0321) showed statistically significant difference only of left hemisphere in male patients with schizophrenia with shallower depth of the sulcus and P100 latency prolongation. Conclusion: The consistency of the findings reveals distinct multiple brain regions, which show changes in the gray matter of patients with chronic forms of schizophrenia. The neurocognitive deficits of schizophrenia show highly consistent cross-sectional relationships to each type of functional outcome.
Keywords: neuropathology; neuroradiology; neurophysiology; visual pathway